The Protective Effects of Metformin and Vitamin C and Their Co-Administration in Bleomycin-Induced Pulmonary Fibrosis in Mice - Mohammad Ebrahim Abbaszadeh; Mohammad Rafi Khezri; Morteza Ghasemnejad-Berenji (Advances in Pharmacological and Pharmaceutical Sciences)
Bleomycin, an antibacterial antibiotic, is used in chemotherapy and is effective against various forms of human carcinomas. However, its use is limited due to its tendency to cause pulmonary fibrosis. Oxidative stress and excessive expression of TGF beta occur in pulmonary fibrosis, leading to cellular death, inflammation, and additional damage to lung tissue. Metformin has the ability to reduce oxidative stress and lower the level of TGF beta by activating AMPK. Additionally, ascorbic acid possesses potent antioxidant characteristics. Consequently, we decided to investigate the effects of these two medications on pulmonary fibrosis and compare with methyl prednisolone. Thirty-six adult mice were categorized into 6 distinct groups: Control, bleomycin (bleo), bleo + methyl prednisolone, bleo + metformin, bleo + ascorbic acid, bleo + metformin + ascorbic acid. Pulmonary fibrosis was induced by the administration of bleomycin in all groups, except for the control group. Subsequently, medications were administered for a duration of 14 days. Ultimately, the mice were sacrificed and lung tissues were obtained for biochemical and histological examination. As shown by biochemical and histological analysis, all treatment groups showed a decrease in oxidative stress factors, inflammation, and lung tissue fibrosis; however, the effects of administering metformin and ascorbic acid together were noticeable. Our study found that administering metformin and ascorbic acid over a period of 14 days, either alone or in combination, may contribute to the repair of pulmonary fibrosis. However, our data indicate that the combined therapy of these drugs provided a better result.